Systematic Review of Systemic Corticosteroid Effects on Patch Testing. Issue 6 (18th November 2022) - Kim-Lim, Penelope; Wennberg, Ebba; Van Noord, Megan; Hastings, Lauren W.; Sullivan, Sydney D.; Huang, Victor; Wu, Peggy A.
Abstract: Systemic corticosteroids are commonly used as a short-term management option for inflammatory skin conditions, such as contact dermatitis. The purpose of our systematic review was to compare presence and degree of patch test reactions with or without different doses of systemic corticosteroid therapy. The relationship between 20, 30, and 40 mg daily doses of prednisone and retained, diminished, and negated reactions was not linear, whereas the reaction ratings for all patches placed with or without corticosteroid therapy revealed trends toward lower intensity reactions while receiving prednisone ( P < 0.0001, χ 2, for all doses of prednisone). Our review provides insight into directions for future studies that examine the effect of corticosteroids on patch testing.